The Impact of Design and Operational Characteristics on Camshafts Reliability - Huseynov, A.G.; Abbasov, V.A.; Asadov, Sh.N.; Kerimov, A.F. (Herald of Azerbaijan Engineering Academy, 2024)
The article examines the operating principles of the gas distribution mechanisms (GCM) of the internal combustion engines (ICE) and the impact of the operational characteristics of the ICE on the reliability of the main parts. The aim of study is a gas camshaft. A comparative topographic analysis of the main factors affecting the operational reliability of gas camshaft tis conducted, and their deficiencies were occuring in production and operation are revealed. The main goal is to investigate the working principle, construction, operational characteristics of the gas distribution mechanism of ICE and the effect on the wear of their parts. In order to increase the reliability and resource of the gas distribution mechanisms, which is the main part of the gas distribution system, the scientific research papers and the literature were investigated to improve its dynamics and structural parameters.